The new documents in Mycenean Greek, Volume one, Introductory essays : drawings of selected tablets - Killen, John T. 1925- (Cambridge University Press, 2024)
In 1952 Michael Ventris deciphered the script found on the Linear B tablets from Crete and the Greek mainland, therefore revealing the earliest known form of Greek. In 1956 he and John Chadwick published Documents in Mycenaean Greek, which gave an account of the decipherment, of the language of the tablets, of the society and economy revealed by the documents and a series of chapters giving texts, translations and commentary of the most important tablets. Though partially updated in 1973, Documents is now very much outdated: there has been a vast accrual of bibliography on the subject since 1973, and discoveries of tablets at new sites. This new survey, written by fourteen of the world's leading experts, will bring the reader fully up-to-date with developments in all aspects of Mycenaean studies, concluding with a new, full glossary of all the most recently discovered words